ESCRT III Regulates Lysosomal Perinuclear Clustering by Inhibiting Kinesin 1 Leading to Agnps Cytotoxicity in Human Cells - Tiantian Liu; Aiguo Xie; Chao Xing; RuiZhe He; Wei Ni; Yinbo Peng; Peng Xu; Yong Fang (Advanced Materials Interfaces)
Abstract Silver nanoparticles (AgNPs) are recognized for their strong antibacterial properties, particularly in applications such as wound and burn treatment; however, the mechanisms of AgNP‐induced cytotoxicity remain  inadequately defined. This study investigates the role of lysosomal dysfunction in AgNP‐induced cytotoxicity, focusing on lysosomal perinuclear clustering (LPC) and its relationship with cellular apoptosis. Human fibroblast HS27 cells are treated with 24 µg mL−1 AgNPs over 48 h, and lysosomal dynamics, cellular localization, and apoptosis rates are analyzed through confocal microscopy and flow cytometry. Protein expression levels of charged multivesicular body protein 4B(CHMP4B) and Kinesin 1, which are central to lysosomal transport and membrane repair, are examined via western blotting. The findings reveal that AgNP exposure leads to LPC and an increase in apoptosis in a time‐dependent manner, accompanied by reduced Kinesin 1 expression. Further, inhibition of CHMP4B and Kinesin 1 significantly promoted apoptosis, while their overexpression mitigated AgNP‐induced cytotoxic effects, underscoring their essential roles in lysosomal integrity. This study provides new insights into the cellular pathways of AgNP‐induced cytotoxicity, focusing on lysosomal transport disruption, and suggests potential molecular targets to reduce adverse effects in therapeutic applications. These results lay a foundation for optimizing AgNP efficacy and improving their safety profile in clinical settings.